Flow injection amperometric detection and off-line sequential extraction column for fractionation of phosphorus in sediment - Pimporn Insain (2018)
© 2017, Chiang Mai University. All rights reserved. Flow injection amperometric system has been developed for determination of phosphorus. It is based on in-line formation of 12-molybdophosphate complex, which is further electrochemically reduced on a glassy carbon working electrode at a constant applied potential of 0.20 V vs. Ag/AgCl. An electrical current is directly proportional to phosphate concentration. Calibration graphs plotting between peak height and phosphate concentration were obtained in range of 0.1-1.0 and 1.0-10.0 mg L -1 P-PO 4 , with a detection limit of 0.03 mg L -1 P-PO 4 . The precision of 2.1, 2.6, 1.5, 1.2 and 1.0% (n=11, 0.1, 0.5, 1.0, 5.0 and 10.0 mg L -1 P-PO 4 , respectively) and sample throughput of 90 h -1 were achieved. The method has lower interferences (i.e., from silicate, colored and colloidal substances, and the Schlieren’s effect) than the commonly used spectrophotometric method. Although it may be interfered by cations, e.g., Fe 3+ and Al 3+ , these ions could be eliminated by using Chelex 100 resin column. The proposed system was successfully applied to determine phosphorus that sequentially leached from sediments. An off-line leaching column was proposed for fractionation of phosphorus according to Hieltjes-Lijklema scheme (HLS), employing 1.0 M NH 4 Cl, 0.1 M NaOH, and 0.5 M HCl as extractants, respectively. The results obtained from extraction by using the proposed column method and the batch shaking method were in good agreement (no significant difference at 95% confident level).